Active Intrapartum SARS-CoV-2 Infection and Pregnancy Outcomes - Nunes, Marta C; Jones, Stephanie; Strehlau, Renate; Baba, Vuyelwa; Ditse, Zanele; da Silva, Kelly; Bothma, Lané; Serafin, Natali; Baillie, Vicky L; Kwatra, Gaurav; Burke, Megan; Wise, Amy; et al. (American journal of perinatology, 2022)
Severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection during pregnancy has been associated with poor pregnancy outcomes. There is, however, not much information on the impact of the timing of SARS-CoV-2 infection on pregnancy outcomes, and studies from low-middle income settings are also scarce. We conducted a cross-sectional study from April to December 2020, in South Africa, to assess the association of SARS-CoV-2 infection on a nasal swab at the time of labor with fetal death, preterm birth, low birth weight, or pregnancy-induced complications. When possible, maternal blood, cord blood, and placenta were collected. SARS-CoV-2 infection was investigated by a nucleic acid amplification test (NAAT). Overall, 3,117 women were tested for SARS-CoV-2 on a nasal swab, including 1,562 (50%) healthy women with uncomplicated term delivery. A positive NAAT was detected among 132 (4%) women. Adverse birth outcomes or pregnancy-related complications were not associated with SARS-CoV-2 infection at the time of labor. Among SARS-CoV-2-infected women, an NAAT-positive result was also obtained from 6 out of 98 (6%) maternal blood samples, 8 out of 93 (9%) cord-blood samples, 14 out of 54 (26%) placentas, and 3 out of 22 (14%) nasopharyngeal swabs from newborns collected within 72 hours of birth. Histological assessment of placental tissue revealed that women with SARS-CoV-2 nasal infection had a higher odds (3.82, 95% confidence interval: 1.20, 12.19) of chronic chorioamnionitis compared with those without SARS-CoV-2 infection. Our study demonstrates that intrapartum, SARS-CoV-2 infection was not associated with evaluated poor outcomes. In utero fetal and placental infections and possible vertical and/or horizontal viral transfer to the newborn were detected among women with nasal SARS-CoV-2 infection. · Intrapartum SARS-CoV-2 infection was not associated with evaluated poor outcomes.. · In utero fetal and placental infections were detected among women with nasal SARS-CoV-2 infection.. · Women with SARS-CoV-2 nasal infection had a higher odds of chronic chorioamnionitis..